2015
DOI: 10.1371/journal.pone.0141339
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Mapping of Yield and Grain Quality Traits in Winter Wheat Genotypes

Abstract: The main goal of this study was to investigate the genetic basis of yield and grain quality traits in winter wheat genotypes using association mapping approach, and identify linked molecular markers for marker assisted selection. A total of 120 elite facultative/winter wheat genotypes were evaluated for yield, quality and other agronomic traits under rain-fed and irrigated conditions for two years (2011–2012) at the Tel Hadya station of ICARDA, Syria. The same genotypes were genotyped using 3,051 Diversity Arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 64 publications
3
73
1
Order By: Relevance
“…and exploit the high marker coverage and higher resolution of the new genotyping technologies without the time and effort needed to develop biparental mapping populations (Crossa et al, 2007). Breseghello and Sorrells (2006) and Tadesse et al (2015), among many others, identified significantly associated markers with kernel size and milling quality in winter wheat. Breseghello and Sorrells (2006) and Tadesse et al (2015), among many others, identified significantly associated markers with kernel size and milling quality in winter wheat.…”
Section: Heat-tolerant Qtls Associated With Grain Yield and Its Compomentioning
confidence: 99%
See 1 more Smart Citation
“…and exploit the high marker coverage and higher resolution of the new genotyping technologies without the time and effort needed to develop biparental mapping populations (Crossa et al, 2007). Breseghello and Sorrells (2006) and Tadesse et al (2015), among many others, identified significantly associated markers with kernel size and milling quality in winter wheat. Breseghello and Sorrells (2006) and Tadesse et al (2015), among many others, identified significantly associated markers with kernel size and milling quality in winter wheat.…”
Section: Heat-tolerant Qtls Associated With Grain Yield and Its Compomentioning
confidence: 99%
“…Several MTA studies have been performed in wheat to identify closely linked molecular markers that could be used for marker-assisted selection and thereby increase the efficiency of conventional breeding efforts in pyramiding genes of interest in desired cultivars (Pinto et al, 2010;Edae et al, 2014;Tadesse et al, 2015;Ogbonnaya et al, 2017). However, it is well known that traits controlled mostly by major genes such as plant height and phenology can have a confounding effect over wheat performance-related traits (Olivares-Villegas et al, 2007;Lopes et al, 2012).…”
Section: Marker-trait Associationsmentioning
confidence: 99%
“…Our population size was smaller than several other studies, which may have lowered the power of QTL detection (Yu et al, 2008). However, we used more stringent parameters to minimize false positives, including the use of more stringent threshold p-values (p £ 10 −5 ) for claiming significant marker-trait association than several other studies that only used p £ 10 −3 (Kollers et al, 2013;Gurung et al, 2014;Kollers et al, 2014;Zegeye et al, 2014;Tadesse et al, 2015) and/or the use of more PCs, accounting for ~50% of the variation for population structure as compared with several other studies that used PCs accounting for lower variation (Gurung et al, 2014;Winkler et al, 2016). Results from this study provide additional information to wheat researchers developing disease-resistant and Ptr toxin-insensitive spring wheat cultivars.…”
Section: Marker-trait Association Analysismentioning
confidence: 99%
“…GWAS has several advantages over traditional QTL analysis, such as higher diversity, better utility of the identified QTL across diverse germplasm, and reduced time required for population development [1012]. GWAS has been successfully employed in many plants, such as Arabidopsis [13], maize [10, 14], barley [15, 16], wheat [17, 18], rice [19], oat [20], sorghum [21] and soybean [11, 22]. In cotton, a few genetic studies using GWAS have been reported [2, 4, 23, 24].…”
Section: Introductionmentioning
confidence: 99%